Rapid and sensitive SARS-CoV-2 detection using a homogeneous fluorescent immunosensor Quenchbody with crowding agents. Issue 22 (7th October 2022) - Zhu, Bo; Nosaka, Nobuyuki; Kanamaru, Shuji; Dong, Jinhua; Dai, Yancen; Inoue, Akihito; Yang, Yinghui; Kobayashi, Kaori; Kitaguchi, Tetsuya; Iwasaki, Hiroshi; Koike, Ryuji; Wakabayashi, Kenji; et al.
Abstract : A Quenchbody immunosensor for SARS-CoV-2 nucleocapsid protein was developed, and 5% PEG6000 significantly improved its response speed and sensitivity. Positive and negative groups of COVID-19 clinical samples were distinguished. Abstract : Antigen tests for SARS-CoV-2 are widely used by the public during the ongoing COVID-19 pandemic, which demonstrates the societal impact of homogeneous immunosensor-related technologies. In this study, we used the PM Q-probe and Quenchbody technologies to develop a SARS-CoV-2 nucleocapsid protein (N protein) homogeneous immunosensor based on a human anti-N protein antibody. For the first time, we uncovered the crowding agent's role in improving the performance of the double-labeled Quenchbody, and the possible mechanisms behind this improvement are discussed. The 5% polyethylene glycol 6000 significantly improved both the response speed and sensitivity of SARS-CoV-2 Quenchbodies. The calculated limit of detection for recombinant N protein was 191 pM (9 ng mL −1 ) within 15 min of incubation, which was 9- to 10-fold lower than the assay without adding crowding agent. We also validated the developed immunosensor in a point-of-care test by measuring specimens from COVID-19-positive patients using a compact tube fluorometer. In brief, this work shows the feasibility of Quenchbody homogeneous immunosensors as rapid and cost-efficient tools for the diagnosis and high-throughput analysis of swab samples in large-scale monitoring and epidemiological studies of COVID-19 or other emerging infectious diseases.